Sophocles and Alcibiades : Athenian Politics in Ancient Greek Literature. - Vickers, Michael (Taylor and Francis, 2014)
Literary historians have long held the view that the plays of the Greek dramatist, Sophocles deal purely with archetypes of the heroic past and that any resemblance to contemporary events or individuals is purely coincidental. In this book, Michael Vickers challenges this view and argues that Sophocles makes regular and extensive allusion to Athenian politics in his plays, especially to Alcibiades, one of the most controversial Athenian politicians of his day. Vickers shows that Sophocles was no closeted intellectual but a man deeply involved in politics and he reminds us that Athenian politics.